Genistein contributes to cell cycle progression and regulates oxidative stress in primary culture of osteoblasts along with osteoclasts attenuation - Siddiqui, Sahabjada (BMC Complement Med Ther, 2020)
BACKGROUND: The present study was designed to examine the role of isoflavone genistein (GS) on bone formation, regulating oxidative stress and cell cycle in primary osteoblasts, as well as attenuation of osteoclast formation. METHODS: Primary calvaria osteoblasts were isolated from 2 to 3 days old neonatal rat pups (n = 6–8) of Sprague Dawley rats. Osteoblasts were incubated with varying concentrations of GS and different assays viz. cell proliferation, differentiation, calcium deposition, cell cycle progression, antioxidant ability, and osteogenic gene expression were performed. Tartrate-resistant acid phosphatase (TRAP) staining and immunolocalization of cathepsin K protein were assessed in bone marrow-derived osteoclasts. RESULTS: Results revealed that GS markedly induced cell growth and osteoblast differentiation depending upon dose. The fluorescent dye DCFH-DA staining data proved the antioxidant ability of GS, which reduced the H(2)O(2)- induced intracellular oxidative stress in osteoblasts. Quantitative real-time PCR analysis revealed that GS treatment upregulated the expression of osteoblastic genes of Runt-related transcription factor 2 (Runx2), bone morphogenetic proteins 2 (BMP2), and osteocalcin. Immunolocalization of BMP2 also indicated the osteogenic efficacy of GS. Furthermore, TRAP staining and cathepsin K expression depicted that GS inhibited multinucleated osteoclasts formation. CONCLUSIONS: In conclusion, GS isoflavone might impart protective effects against oxidative stress-induced bone loss and thus, could maintain skeletal growth.